Motivation and Organizational Climate in employees of university entities - Palma Carrillo, Sonia (2000)
The present survey studies the motivation and organizational climate in university centers. The sample consisted of 473 full time professors and employees in three private universities of Lima, Perú. Two scales were used for testing the motivation and organizational climate on the McClelland and Litwing approach were used. The validation and the reliability of the instruments with the respective analysis were shown. The data was processed using the SPSS software for the statistic analysis. The results show medium level motivation and organizational climate and differences only regarding organizational motivation with professors and workers with more than five years in the institution. Such differences were not found with the climate organizational. They need of adequate managment when deciding the courses of action and the comunicative systems to optimize the organizational output is highlightened.